2.2.125 Problems 12401 to 12500

Table 2.251: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

12401

\[ {}y y^{\prime }-y = a^{2} f^{\prime }\left (x \right ) f^{\prime \prime }\left (x \right )-\frac {\left (f \left (x \right )+b \right )^{2} f^{\prime \prime }\left (x \right )}{{f^{\prime }\left (x \right )}^{3}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

2.365

12402

\[ {}y y^{\prime } = \left (a x +b \right ) y+1 \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

0.937

12403

\[ {}y y^{\prime } = \frac {y}{\left (a x +b \right )^{2}}+1 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.631

12404

\[ {}y y^{\prime } = \left (a -\frac {1}{a x}\right ) y+1 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.909

12405

\[ {}y y^{\prime } = \frac {y}{\sqrt {a x +b}}+1 \]

[[_1st_order, _with_linear_symmetries], [_Abel, ‘2nd type‘, ‘class B‘]]

9.444

12406

\[ {}y y^{\prime } = \frac {3 y}{\sqrt {a \,x^{{3}/{2}}+8 x}}+1 \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

3.286

12407

\[ {}y y^{\prime } = \left (\frac {a}{x^{{2}/{3}}}-\frac {2}{3 a \,x^{{1}/{3}}}\right ) y+1 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.750

12408

\[ {}y y^{\prime } = a \,{\mathrm e}^{\lambda x} y+1 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.125

12409

\[ {}y y^{\prime } = \left (a \,{\mathrm e}^{\lambda x}+b \,{\mathrm e}^{-\lambda x}\right ) y+1 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.657

12410

\[ {}y y^{\prime } = a y \cosh \left (x \right )+1 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.789

12411

\[ {}y y^{\prime } = a y \sinh \left (x \right )+1 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.980

12412

\[ {}y y^{\prime } = a \cos \left (\lambda x \right ) y+1 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.046

12413

\[ {}y y^{\prime } = a \sin \left (\lambda x \right ) y+1 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.220

12414

\[ {}y y^{\prime } = \left (a x +3 b \right ) y+c \,x^{3}-a b \,x^{2}-2 b^{2} x \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.732

12415

\[ {}y y^{\prime } = \left (3 a x +b \right ) y-a^{2} x^{3}-a b \,x^{2}+c x \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.042

12416

\[ {}2 y y^{\prime } = \left (7 a x +5 b \right ) y-3 a^{2} x^{3}-2 c \,x^{2}-3 b^{2} x \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.515

12417

\[ {}y y^{\prime } = \left (\left (3-m \right ) x -1\right ) y-\left (m -1\right ) a x \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.152

12418

\[ {}y y^{\prime }+x \left (a \,x^{2}+b \right ) y+x = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.145

12419

\[ {}y y^{\prime }+a \left (1-\frac {1}{x}\right ) y = a^{2} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.871

12420

\[ {}y y^{\prime }-a \left (1-\frac {b}{x}\right ) y = a^{2} b \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.927

12421

\[ {}y y^{\prime } = x^{n -1} \left (\left (2 n +1\right ) x +a n \right ) y-n \,x^{2 n} \left (x +a \right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.866

12422

\[ {}y y^{\prime } = a \left (-n b +x \right ) x^{n -1} y+c \left (x^{2}-\left (2 n +1\right ) b x +n \left (n +1\right ) b^{2}\right ) x^{2 n -1} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.537

12423

\[ {}y y^{\prime } = \left (a \left (2 n +k \right ) x^{k}+b \right ) x^{n -1} y+\left (-a^{2} n \,x^{2 k}-a b \,x^{k}+c \right ) x^{2 n -1} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

41.776

12424

\[ {}y y^{\prime } = \left (a \left (2 n +k \right ) x^{2 k}+b \left (2 m -k \right )\right ) x^{m -k -1} y-\frac {a^{2} m \,x^{4 k}+c \,x^{2 k}+b^{2} m}{x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

62.603

12425

\[ {}y y^{\prime } = \frac {\left (\left (m +2 L -3\right ) x +n -2 L +3\right ) y}{x}+\left (\left (m -L -1\right ) x^{2}+\left (n -m -2 L +3\right ) x -n +L -2\right ) x^{1-2 L} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

14.283

12426

\[ {}y y^{\prime } = \left (a \left (2 n +1\right ) x^{2}+c x +b \left (2 n -1\right )\right ) x^{n -2} y-\left (n \,a^{2} x^{4}+a c \,x^{3}+n \,b^{2}+b c x +d \,x^{2}\right ) x^{2 n -3} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

8.967

12427

\[ {}y y^{\prime } = \left (a \left (n -1\right ) x +b \left (2 \lambda +n \right )\right ) x^{\lambda -1} \left (a x +b \right )^{-\lambda -2} y-\left (a n x +b \left (\lambda +n \right )\right ) x^{2 \lambda -1} \left (a x +b \right )^{-2 \lambda -3} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

28.644

12428

\[ {}y y^{\prime }-\frac {a \left (\left (m -1\right ) x +1\right ) y}{x} = \frac {a^{2} \left (m x +1\right ) \left (x -1\right )}{x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.196

12429

\[ {}y y^{\prime }-a \left (1-\frac {b}{\sqrt {x}}\right ) y = \frac {a^{2} b}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.343

12430

\[ {}y y^{\prime } = \frac {3 y}{\left (a x +b \right )^{{1}/{3}} x^{{5}/{3}}}+\frac {3}{\left (a x +b \right )^{{2}/{3}} x^{{7}/{3}}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

6.000

12431

\[ {}3 y y^{\prime } = \frac {\left (-7 \lambda s \left (3 s +4 \lambda \right ) x +6 s -2 \lambda \right ) y}{x^{{1}/{3}}}+\frac {6 \lambda s x -6}{x^{{2}/{3}}}+2 \left (\lambda s \left (3 s +4 \lambda \right ) x +5 \lambda \right ) \left (-\lambda s \left (3 s +4 \lambda \right ) x +3 s +4 \lambda \right ) x^{{1}/{3}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

21.140

12432

\[ {}y y^{\prime }+\frac {a \left (6 x -1\right ) y}{2 x} = -\frac {a^{2} \left (x -1\right ) \left (4 x -1\right )}{2 x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.210

12433

\[ {}y y^{\prime }-\frac {a \left (1+\frac {2 b}{x^{2}}\right ) y}{2} = \frac {a^{2} \left (3 x +\frac {4 b}{x}\right )}{16} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.599

12434

\[ {}y y^{\prime }+\frac {a \left (13 x -20\right ) y}{14 x^{{9}/{7}}} = -\frac {3 a^{2} \left (x -1\right ) \left (x -8\right )}{14 x^{{11}/{17}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

80.126

12435

\[ {}y y^{\prime }+\frac {5 a \left (23 x -16\right ) y}{56 x^{{9}/{7}}} = -\frac {3 a^{2} \left (x -1\right ) \left (25 x -32\right )}{56 x^{{11}/{17}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

99.704

12436

\[ {}y y^{\prime }+\frac {a \left (19 x +85\right ) y}{26 x^{{18}/{13}}} = -\frac {3 a^{2} \left (x -1\right ) \left (x +25\right )}{26 x^{{23}/{13}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

23.154

12437

\[ {}y y^{\prime }+\frac {a \left (13 x -18\right ) y}{15 x^{{7}/{5}}} = -\frac {4 a^{2} \left (x -1\right ) \left (x -6\right )}{15 x^{{9}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.113

12438

\[ {}y y^{\prime }+\frac {a \left (5 x +1\right ) y}{2 \sqrt {x}} = a^{2} \left (-x^{2}+1\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.481

12439

\[ {}y y^{\prime }+\frac {3 a \left (19 x -14\right ) x^{{7}/{5}} y}{35} = -\frac {4 a^{2} \left (x -1\right ) \left (9 x -14\right ) x^{{9}/{5}}}{35} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.418

12440

\[ {}y y^{\prime }+\frac {3 a \left (3 x +7\right ) y}{10 x^{{13}/{10}}} = -\frac {a^{2} \left (x -1\right ) \left (x +9\right )}{5 x^{{8}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

79.074

12441

\[ {}y y^{\prime }+\frac {a \left (7 x -12\right ) y}{10 x^{{7}/{5}}} = -\frac {a^{2} \left (x -1\right ) \left (x -16\right )}{10 x^{{9}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.435

12442

\[ {}y y^{\prime }+\frac {3 a \left (13 x -8\right ) y}{20 x^{{7}/{5}}} = -\frac {a^{2} \left (x -1\right ) \left (27 x -32\right )}{20 x^{{9}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.514

12443

\[ {}y y^{\prime }+\frac {3 a \left (3 x +11\right ) y}{14 x^{{10}/{7}}} = -\frac {a^{2} \left (x -1\right ) \left (x -27\right )}{14 x^{{13}/{7}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.671

12444

\[ {}y y^{\prime }-\frac {a \left (x +1\right ) y}{2 x^{{7}/{4}}} = \frac {a^{2} \left (x -1\right ) \left (3 x +5\right )}{4 x^{{5}/{2}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

24.288

12445

\[ {}y y^{\prime }-\frac {a \left (x +1\right ) y}{2 x^{{7}/{4}}} = \frac {a^{2} \left (x -1\right ) \left (x +5\right )}{4 x^{{5}/{2}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

24.585

12446

\[ {}y y^{\prime }-\frac {a \left (4 x +3\right ) y}{14 x^{{8}/{7}}} = -\frac {a^{2} \left (x -1\right ) \left (16 x +5\right )}{14 x^{{9}/{7}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.068

12447

\[ {}y y^{\prime }+\frac {a \left (13 x -3\right ) y}{6 x^{{2}/{3}}} = -\frac {a^{2} \left (x -1\right ) \left (5 x -1\right )}{6 x^{{1}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

12.364

12448

\[ {}y y^{\prime }-\frac {a \left (8 x -1\right ) y}{28 x^{{8}/{7}}} = \frac {a^{2} \left (x -1\right ) \left (32 x +3\right )}{28 x^{{9}/{7}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.253

12449

\[ {}y y^{\prime }-\frac {a \left (5 x -4\right ) y}{x^{4}} = \frac {a^{2} \left (x -1\right ) \left (3 x -1\right )}{x^{7}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.638

12450

\[ {}y y^{\prime }-\frac {2 a \left (3 x -10\right ) y}{5 x^{4}} = \frac {a^{2} \left (x -1\right ) \left (8 x -5\right )}{5 x^{7}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.674

12451

\[ {}y y^{\prime }+\frac {a \left (39 x -4\right ) y}{42 x^{{9}/{7}}} = -\frac {a^{2} \left (x -1\right ) \left (9 x -1\right )}{42 x^{{11}/{7}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.093

12452

\[ {}y y^{\prime }+\frac {a \left (x -2\right ) y}{x} = \frac {2 a^{2} \left (x -1\right )}{x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.130

12453

\[ {}y y^{\prime }+\frac {a \left (3 x -2\right ) y}{x} = -\frac {2 a^{2} \left (x -1\right )^{2}}{x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.681

12454

\[ {}y y^{\prime }+\frac {a \left (1-\frac {b}{x^{2}}\right ) y}{x} = \frac {a^{2} b}{x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.454

12455

\[ {}y y^{\prime }-\frac {a \left (3 x -4\right ) y}{4 x^{{5}/{2}}} = \frac {a^{2} \left (x -1\right ) \left (x +2\right )}{4 x^{4}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.138

12456

\[ {}y y^{\prime }+\frac {a \left (33 x +2\right ) y}{30 x^{{6}/{5}}} = -\frac {a^{2} \left (x -1\right ) \left (9 x -4\right )}{30 x^{{7}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.279

12457

\[ {}y y^{\prime }-\frac {a \left (x -8\right ) y}{8 x^{{5}/{2}}} = -\frac {a^{2} \left (x -1\right ) \left (3 x -4\right )}{8 x^{4}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.285

12458

\[ {}y y^{\prime }+\frac {a \left (17 x +18\right ) y}{30 x^{{22}/{15}}} = -\frac {a^{2} \left (x -1\right ) \left (x +4\right )}{30 x^{{29}/{15}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

77.245

12459

\[ {}y y^{\prime }-\frac {a \left (6 x -13\right ) y}{13 x^{{5}/{2}}} = -\frac {a^{2} \left (x -1\right ) \left (x -13\right )}{26 x^{4}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.008

12460

\[ {}y y^{\prime }+\frac {a \left (24 x +11\right ) x^{{27}/{20}} y}{30} = -\frac {a^{2} \left (x -1\right ) \left (9 x +1\right )}{60 x^{{17}/{10}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

96.272

12461

\[ {}y y^{\prime }-\frac {2 a \left (3 x +2\right ) y}{5 x^{{8}/{5}}} = \frac {a^{2} \left (x -1\right ) \left (8 x +1\right )}{5 x^{{11}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.355

12462

\[ {}y y^{\prime }-\frac {6 a \left (4 x +1\right ) y}{5 x^{{7}/{5}}} = \frac {a^{2} \left (x -1\right ) \left (27 x +8\right )}{5 x^{{9}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.889

12463

\[ {}y y^{\prime }-\frac {a \left (x +4\right ) y}{5 x^{{8}/{5}}} = \frac {a^{2} \left (x -1\right ) \left (3 x +7\right )}{5 x^{{3}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.255

12464

\[ {}y y^{\prime }-\frac {a \left (x +4\right ) y}{5 x^{{8}/{5}}} = \frac {a^{2} \left (x -1\right ) \left (3 x +7\right )}{5 x^{{11}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.202

12465

\[ {}y y^{\prime }-\frac {a \left (2 x -1\right ) y}{x^{{5}/{2}}} = \frac {a^{2} \left (x -1\right ) \left (3 x +1\right )}{2 x^{4}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.421

12466

\[ {}y y^{\prime }+\frac {a \left (x -6\right ) y}{5 x^{{7}/{5}}} = \frac {2 a^{2} \left (x -1\right ) \left (x +4\right )}{5 x^{{9}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.003

12467

\[ {}y y^{\prime }+\frac {a \left (21 x +19\right ) y}{5 x^{{7}/{5}}} = -\frac {2 a^{2} \left (x -1\right ) \left (9 x -4\right )}{5 x^{{9}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

16.983

12468

\[ {}y y^{\prime }-\frac {3 a y}{x^{{7}/{4}}} = \frac {a^{2} \left (x -1\right ) \left (x -9\right )}{4 x^{{5}/{2}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

12.550

12469

\[ {}y y^{\prime }-\frac {a \left (\left (k +1\right ) x -1\right ) y}{x^{2}} = \frac {a^{2} \left (k +1\right ) \left (x -1\right )}{x^{2}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.581

12470

\[ {}y y^{\prime }-a \left (\left (k -2\right ) x +2 k -3\right ) x^{-k} y = a^{2} \left (k -2\right ) \left (x -1\right )^{2} x^{1-2 k} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

6.261

12471

\[ {}y y^{\prime }-\frac {a \left (\left (4 k -7\right ) x -4 k +5\right ) x^{-k} y}{2} = \frac {a^{2} \left (2 k -3\right ) \left (x -1\right )^{2} x^{1-2 k}}{2} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

6.586

12472

\[ {}y y^{\prime }-\left (\left (2 n -1\right ) x -a n \right ) x^{-n -1} y = n \left (x -a \right ) x^{-2 n} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.954

12473

\[ {}y y^{\prime }-\left (\left (n +1\right ) x -a n \right ) x^{n -1} \left (x -a \right )^{-n -2} y = n \,x^{2 n} \left (x -a \right )^{-2 n -3} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

10.679

12474

\[ {}y y^{\prime }-a \left (\left (2 k -3\right ) x +1\right ) x^{-k} y = a^{2} \left (k -2\right ) \left (\left (k -1\right ) x +1\right ) x^{2-2 k} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.192

12475

\[ {}y y^{\prime }-a \left (\left (n +2 k -3\right ) x +3-2 k \right ) x^{-k} y = a^{2} \left (\left (n +k -1\right ) x^{2}-\left (n +2 k -3\right ) x +k -2\right ) x^{1-2 k} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

8.417

12476

\[ {}y y^{\prime }-\frac {a \left (\left (n +2\right ) x -2\right ) x^{-\frac {2 n +1}{n}} y}{n} = \frac {a^{2} \left (\left (n +1\right ) x^{2}-2 x -n +1\right ) x^{-\frac {3 n +2}{n}}}{n} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.424

12477

\[ {}y y^{\prime }-\frac {a \left (\frac {\left (n +4\right ) x}{n +2}-2\right ) x^{-\frac {2 n +1}{n}} y}{n} = \frac {a^{2} \left (2 x^{2}+\left (n^{2}+n -4\right ) x -\left (n -1\right ) \left (n +2\right )\right ) x^{-\frac {3 n +2}{n}}}{n \left (n +2\right )} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

6.691

12478

\[ {}y y^{\prime }+\frac {a \left (\frac {\left (3 n +5\right ) x}{2}+\frac {n -1}{n +1}\right ) x^{-\frac {n +4}{n +3}} y}{n +3} = -\frac {a^{2} \left (\left (n +1\right ) x^{2}-\frac {\left (n^{2}+2 n +5\right ) x}{n +1}+\frac {4}{n +1}\right ) x^{-\frac {n +5}{n +3}}}{2 n +6} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

11.279

12479

\[ {}y y^{\prime }-a \left (\frac {n +2}{n}+b \,x^{n}\right ) y = -\frac {a^{2} x \left (\frac {n +1}{n}+b \,x^{n}\right )}{n} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.925

12480

\[ {}y y^{\prime } = \left (a \,{\mathrm e}^{x}+b \right ) y+c \,{\mathrm e}^{2 x}-a b \,{\mathrm e}^{x}-b^{2} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.595

12481

\[ {}y y^{\prime } = \left (a \left (2 \mu +\lambda \right ) {\mathrm e}^{\lambda x}+b \right ) {\mathrm e}^{\mu x} y+\left (-a^{2} \mu \,{\mathrm e}^{2 \lambda x}-a b \,{\mathrm e}^{\lambda x}+c \right ) {\mathrm e}^{2 \mu x} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

6.085

12482

\[ {}y y^{\prime } = \left (a \,{\mathrm e}^{\lambda x}+b \right ) y+c \left (a^{2} {\mathrm e}^{2 \lambda x}+a b \left (\lambda x +1\right ) {\mathrm e}^{\lambda x}+b^{2} \lambda x \right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

4.314

12483

\[ {}y y^{\prime } = {\mathrm e}^{\lambda x} \left (2 a \lambda x +a +b \right ) y-{\mathrm e}^{2 \lambda x} \left (a^{2} \lambda \,x^{2}+a b x +c \right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

88.332

12484

\[ {}y y^{\prime } = {\mathrm e}^{a x} \left (2 a \,x^{2}+b +2 x \right ) y+{\mathrm e}^{2 a x} \left (-a \,x^{4}-b \,x^{2}+c \right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

5.431

12485

\[ {}y y^{\prime }+a \left (2 b x +1\right ) {\mathrm e}^{b x} y = -a^{2} b \,x^{2} {\mathrm e}^{2 b x} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.498

12486

\[ {}y y^{\prime }-a \left (1+2 n +2 n \left (n +1\right ) x \right ) {\mathrm e}^{\left (n +1\right ) x} y = -a^{2} n \left (n +1\right ) \left (n x +1\right ) x \,{\mathrm e}^{2 \left (n +1\right ) x} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

5.512

12487

\[ {}y y^{\prime }+a \left (1+2 b \sqrt {x}\right ) {\mathrm e}^{2 b \sqrt {x}} y = -a^{2} b \,x^{{3}/{2}} {\mathrm e}^{4 b \sqrt {x}} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

5.036

12488

\[ {}y y^{\prime } = \left (a \cosh \left (x \right )+b \right ) y-a b \sinh \left (x \right )+c \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

8.133

12489

\[ {}y y^{\prime } = \left (a \sinh \left (x \right )+b \right ) y-a b \cosh \left (x \right )+c \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

8.564

12490

\[ {}y y^{\prime } = \left (2 \ln \left (x \right )+a +1\right ) y+x \left (-\ln \left (x \right )^{2}-a \ln \left (x \right )+b \right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.863

12491

\[ {}y y^{\prime } = \left (2 \ln \left (x \right )^{2}+2 \ln \left (x \right )+a \right ) y+x \left (-\ln \left (x \right )^{4}-a \ln \left (x \right )^{2}+b \right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.140

12492

\[ {}y y^{\prime } = a x \cos \left (\lambda \,x^{2}\right ) y+x \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

4.608

12493

\[ {}y y^{\prime } = a x \sin \left (\lambda \,x^{2}\right ) y+x \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

4.879

12494

\[ {}\left (A y+B x +a \right ) y^{\prime }+B y+k x +b = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.666

12495

\[ {}\left (y+a x +b \right ) y^{\prime } = \alpha y+\beta x +\gamma \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

8.302

12496

\[ {}\left (y+a k \,x^{2}+b x +c \right ) y^{\prime } = -a y^{2}+2 a k x y+m y+k \left (k +b -m \right ) x +s \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

6.173

12497

\[ {}\left (y+A \,x^{n}+a \right ) y^{\prime }+n A \,x^{n -1} y+k \,x^{m}+b = 0 \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x),G(x)]‘], [_Abel, ‘2nd type‘, ‘class A‘]]

35.770

12498

\[ {}\left (y+a \,x^{n +1}+b \,x^{n}\right ) y^{\prime } = \left (a n \,x^{n}+c \,x^{n -1}\right ) y \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.834

12499

\[ {}x y y^{\prime } = a y^{2}+b y+c \,x^{n}+s \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.135

12500

\[ {}x y y^{\prime } = -n y^{2}+a \left (2 n +1\right ) x y+b y-a^{2} n \,x^{2}-a b x +c \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.954